Kompleksitas Operasi, Manajemen Laba dan Keterbacaan Laporan Tahunan - Yosi Yulivia; Annisaa Rahman; Denny Yohana (Universitas Batanghari Jambi, 2021)
This study aims to prove empirically the effect of operating complexity and earnings management on the readability of annual reports. The population in this study are all companies listed on the Indonesia Stock Exchange (BEI) during 2016-2017. The sample in this study was selected using purposive sampling technique with a study period of 2 years (2016-2017) in order to obtain 442 observations of data. Operational complexity is measured by the number of natural logarithms of business segments and the number of natural logarithms of geographic segments, earnings management is measured by the Modified Jones Model, readability is measured by the Flesch Reading Ease score. The data analysis technique used is multiple linear regression analysis method. The results of this study indicate that the first hypothesis, operation complexity has effect on the readability of annual reports. The second hypothesis, earnings management has no effect on the readability of annual reports.